2004
DOI: 10.2320/matertrans.45.1140
|View full text |Cite
|
Sign up to set email alerts
|

Laser Welding of Titanium and Dental Precious Alloys

Abstract: The performance of laser welding of Ti and two dental precious alloys (Ag-Pd-Au, Au-Pt-Ag) was investigated by mechanical testing and microscopic observation, using butt joint as design. The laser irradiation was done using a commercial Nd:YAG dental laser-welding device in a single pulse mode with output currents 150, 200, 250, 300 A, spot diameters 0.6, 0.9, 1.2 mm, and pulse duration 10 ms. The average welding fracture strength of the dissimilar metals were 108.9 and 137.2 MPa for Ti and Ag-Pd-Au alloy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The cracks are generated during or after welding, and they are determined by the laser output, spot diameter, and laser beam diameter, [14]. This might explain the difference in the fissures numbers observed between group A and B samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cracks are generated during or after welding, and they are determined by the laser output, spot diameter, and laser beam diameter, [14]. This might explain the difference in the fissures numbers observed between group A and B samples.…”
Section: Discussionmentioning
confidence: 99%
“…Hot cracking susceptibility during welding is usually evaluated when the strain or stress is changed during the process, but the use of a pulsed Nd : YAG laser, where power is continuously decreased with time, may control the rate of solidification and can effectively reduce hot cracking in alloys [ 13 ]. The cracks are generated during or after welding, and they are determined by the laser output, spot diameter, and laser beam diameter, [ 14 ]. This might explain the difference in the fissures numbers observed between group A and B samples.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in fracture toughness is due to the cracks and pores formed in the weld zones and this is the result of insufficient melting and mixture between components with different properties. Resulting low strength weld joint are considered to be the consequences of cracks, porosity and precipitates generated in the welded region [ 90 ]. Nishio et al also investigated several dental alloys for evaluating the performance of the butt joint.…”
Section: Laser Welding Of Dental Alloysmentioning
confidence: 99%
“…Berg et al 5) found that the presence of large pores (a few hundreds of m in diameter) in the weld metal appeared to be the most important factor in influencing the strength of laser-welded Ti joints. Similarly, in a study by Iwasaki et al 14) on the performance of laser-welded Ti and dental precious alloys by mechanical testing, they arrived at the same conclusion. The authors found that porosity in the weld zone was the cause for lower welding fracture strength of dissimilar metals as compared with similar metals 14) .…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, in a study by Iwasaki et al 14) on the performance of laser-welded Ti and dental precious alloys by mechanical testing, they arrived at the same conclusion. The authors found that porosity in the weld zone was the cause for lower welding fracture strength of dissimilar metals as compared with similar metals 14) . In this study, however, the four-point bending test results showed that the presence of voids (from a few tens to hundreds of m in diameter) in the weld metal with various welding pulse energies (11 24 J) had no detrimental influence on the fracture resistance of cast Ti plate joints (thickness: 1 3 mm).…”
Section: Discussionmentioning
confidence: 57%